POLITENESS STRATEGIES ON SOCIAL MEDIA - Risti Yani Rahmawati (La Tansa Mashiro, 2022)
People are becoming more drawn to social media as a result of the rapid advancement of technology in this era of globalization. We still require manners when using social media, just like when speaking to people in person. The purpose of this study was to examine the politeness techniques employed in Facebook group chat. The study discussed the applications of the politeness techniques employed in Facebook group chat. Based on Brown and Levinson's (1987) taxonomy of related politeness tactics, the study was descriptively examined. The information was examined and put into the classification. The findings indicated that the majority of group chat participants utilized positive politeness, followed by negative politeness, off-the-record technique, and bald on record method as the least common. The findings of this study demonstrated how crucial politeness is in written communication. It can be used to lessen misunderstandings when utilizing social media.